2009
DOI: 10.12968/hmed.2009.70.7.43138
|View full text |Cite
|
Sign up to set email alerts
|

Should patients be manually ventilated during rapid sequence induction of anaesthesia?

Abstract: Pulmonary aspiration of gastric contents has been recognized as a cause of significant morbidity and mortality during anaesthesia since the classic publication by Mendelson in 1946. The introduction of suxamethonium 5 years later allowed tracheal intubation to be achieved under complete muscle relaxation within 1 minute of induction of anaesthesia. In 1961 Sellick described the use of cricoid pressure to prevent gastric regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Advocates for this traditional approach claim that gastric insufflation can occur with PPV, thus increasing the likelihood of regurgitation and aspiration before securing the airway. 71 Manual bag-mask ventilation did not result in gastric insufflation when airway pressures were kept Ͻ15 cm H 2 O even in the absence of CP. Whereas some authors clearly stressed that PPV is contraindicated, 37 others found it acceptable.…”
Section: Manual Ventilationmentioning
confidence: 94%
See 1 more Smart Citation
“…Advocates for this traditional approach claim that gastric insufflation can occur with PPV, thus increasing the likelihood of regurgitation and aspiration before securing the airway. 71 Manual bag-mask ventilation did not result in gastric insufflation when airway pressures were kept Ͻ15 cm H 2 O even in the absence of CP. Whereas some authors clearly stressed that PPV is contraindicated, 37 others found it acceptable.…”
Section: Manual Ventilationmentioning
confidence: 94%
“…71 Advocates of the use of PPV argue that avoiding the risk of hypoxemia at this point outweighs the potential risk of gastric insufflation. Hypoxemia can develop in obese, pregnant, pediatric, and critically ill patients before tracheal intubation is accomplished, or in the true emergent situations in which effective oxygen administration (denitrogenation) cannot be completed satisfactorily.…”
Section: Manual Ventilationmentioning
confidence: 99%
“…Indications for this technique include patients at risk of rapid development of hypoxaemia (e.g., in those critically ill, morbidly obese or pregnant), in emergency situations where preoxygenation cannot be satisfactorily completed or when a longer time to achieve tracheal intubation is anticipated. Although the effect of positive pressure ventilation with the application of cricoid pressure in terms of gastric insufflation of air is not definitively known, gentle positive pressure ventilation with an inspiratory pressure < 20 cm H 2 O in combination with cricoid pressure may be acceptable in these clinical scenarios [25]. Positive pressure ventilation via a face mask may also be provided before and after administration of a muscle relaxant for patients unable to tolerate the brief period of apnoea associated with RSII.…”
Section: Modified Rapid Sequence Inductionmentioning
confidence: 99%
“…This, combined with gentle manual ventilation of of the lungs for all patients soon after induction, would reduce the likelihood of early desaturation. The theoretical risk of stomach inflation caused by gentle manual ventilation is, in our opinion, outweighed by the certain benefit of maintaining adequate oxygenation . Furthermore, inadequate inflation of the chest whilst attempting gentle bag‐mask ventilation could indicate airway maintenance problems at an early stage, and allow senior help to be sought more promptly.…”
mentioning
confidence: 99%
“…Reluctance to use manual ventilation during ‘traditional’ rapid sequence induction leaves the patient at the point of rapid desaturation during the first intubation attempt, compounding an already stressful situation. Anxiety about maternal or fetal hypoxia can tempt anaesthetists to intubate before optimal paralysis has been achieved, increasing the likelihood of intubation difficulties .…”
mentioning
confidence: 99%